A dynamic general equilibrium analysis of adaptation to climate change in Ethiopia - Robinson, Sherman; Willenbockel, Dirk; Strzepek, Kenneth M. (Wiley, 2012)
This study links a multisectoral, regionalized, dynamic, computable general equilibrium (CGE) model of Ethiopia with a system country-specific hydrology, crop, road, and hydropower engineering models to simulate the economic impacts of climate change scenarios from global circulation models (GCMs) to 2050. In the absence of externally funded, policy-driven adaptation investments, Ethiopia's GDP in 2050 will be up to 10% below the counterfactual no climate change (historical climate) baseline. Suitably designed adaptation investments could restore aggregate welfare to baseline levels at a cost that is substantially lower than the welfare losses as a result of climate change. Such investments, even if funded from domestic resources, have benefits that greatly exceed their costs, and are largely consistent with Ethiopia's long-run development strategy.